Analisis Kritis Atas Penentuan Dasar Pengenaan Pajak dalam Pemotongan PPH Pasal 23 Atas Jasa Ekspedisi: Studi Kasus pada Pola 'All-In' yang Menginklusi Biaya Operasional di PT MPX Indonesia - Fransisca Anggraeni; Ratna Septiyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to critically analyze the determination of the Tax Base (Dasar Pengenaan Pajak/DPP) in the withholding tax mechanism under Article 23 of the Indonesian Income Tax Law for freight forwarding services at PT MPX Indonesia. The research focuses on evaluating the implementation of the “All-In” billing model, where all operational costs are consolidated into a single gross invoice amount and treated as the taxable base. This approach raises concerns regarding its compliance with applicable tax regulations, particularly in distinguishing between service fees and reimbursable expenses. The study employs a qualitative descriptive method using a case study approach. Data are collected through documentation analysis of transaction records, including invoices and Unified Income Tax withholding receipts. The findings are expected to provide insights into the appropriateness of the applied tax base determination method and its implications for tax compliance and efficiency within the company’s operational practices and financial reporting system.